Physiological Characteristics to Indicate Water Use Efficiency and Drought Tolerance of 30 Indonesian Sorghum [Sorghum bicolor (L.) Moench] Accessions - Wahyu Widiyono; Satya Nugroho (HAYATI Journal of Biosciences, 2023)
Water use efficiency (WUE) is an essential subject in drought-restricted agricultures. Physiological parameters can be used to understand plant efficiencies in water usage. This research aimed to understand the physiological characteristics of 30 Indonesian sorghum accessions (Sorghum bicolor (L.) Moench), which indicate WUE and drought tolerance. Field research was conducted at Cibinong Science Center, National Research and Innovation Agency (BRIN) using Randomized Block Design with 30 sorghum accessions in 3 replicates. Experimental parameters included photosynthetic photon flux density (PPFD), stomatal conductance (GSW), photosynthetic (A) and transpiration (E) rates, and Leaf Area Index (LAI). The WUE was measured using four different approaches: instantaneous WUE (A:E), intrinsic WUE (A:GSW), and the relation between the biomass dry weight (BDW)/A and BDW/E. Based on WUE measurements, we concluded that sorghum accessions could be clustered into five groups, from the most efficient to inefficient water use. We also found that in some cases, WUE based on single leaf measurement had a positive correlation with WUE based on biomass, indicating its sufficiency in determining WUE status. The inconsistencies may be due to different sorghum physiological characteristics regarding gas exchange due to external stimuli (PPFD).